Pengaruh Persepsi Harga dan Kualitas Layanan Terhadap Minat Beli Ulang di Alfamidi Mongiansidi Rantepao - Joris Masarrang; Mey E. Limbongan; Lisa K. Wibisono (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The aim of this research is to determine the influence of perceptions of price and service quality on repurchase interest at Alfamidi. The population in this study were customers of Alfamidi Mongiansidi Rantepao. The data collection scale in this study used observation and questionnaires and the formation scale used a Likert scale. The sampling technique uses Non-Probability Sampling with the purpose sampling method. The number of samples taken was 64 customers. The data used is primary data from questionnaires given to Alfamidi Mongiansidi customers. The results of the research show that perceived price and service quality have a significant impact on repurchase intention. Furthermore, the service quality variable has a significant effect on repurchase interest.